Hybrid Reconnaissance Mission to the 30 October 2020 Aegean Sea Earthquake and Tsunami (Izmir, Turkey & Samos, Greece): Description of Data Collection Methods and Damage - Aktas, Yasemin D.; Ioannou, Ioanna; Malcioglu, Fatma Sevil; Kontoe, Maria; Parammal Vatteri, Ahsana; Baiguera, Marco; Black, Jacob; Kosker, Anil; Dermanis, Panagiotis; Esabalioglou, Martha; Cabuk, Eser; Donmez, Kokcan; et al. (Frontiers in Built Environment, 2022)
On 30 October 2020, an earthquake of Mw 6.9 hit the Aegean coasts of Turkey and Greece. The epicentre was some 14 km northeast of Avlakia on Samos Island, and 25 km southwest of Seferihisar, Turkey, triggering also a tsunami. The event has been followed by >4000 aftershocks up to Mw 5.2. The Earthquake Engineering Field Investigation Team (EEFIT) has immediately gathered a team to conduct a hybrid reconnaissance study, bringing together remote and field investigation techniques. The mission took place between 16 November and 17 December, inclusive of 3 sets of field study carried out by the field crews for building damage assessment in the affected areas in Turkey and Greece under the coordination of the remote team. The mission also aimed to assess the viability of alternative data sources for an appraisal of the future viability of hybrid missions. This paper summarises the mission setup and findings, and discusses the benefits of and difficulties encountered during this hybrid reconnaissance activity.